THEME AND MORAL VALUES IN “CLOSER THAN VEINS” BY OUTLANDISH - Gumilar Sanjaya; Syahfitri Purnama (Universitas Indraprasta PGRI, 2020)
Abstract: This research aims to examine the Theme and Moral Values in